SrTiO3–BaTiO3 nanocomposites with temperature independent permittivity and linear tunability fabricated using field-assisted sintering from chemically synthesized powders. Issue 35 (23rd August 2017) - Airimioaei, M.; Buscaglia, M. T.; Tredici, I.; Anselmi-Tamburini, U.; Ciomaga, C. E.; Curecheriu, L.; Bencan, A.; Buscaglia, V.; Mitoseriu, L.
Abstract : SrTiO3 –BaTiO3 nanocomposite fabricated by high-pressure field-assisted sintering exhibits temperature-stable dielectric permittivity, low losses and acceptable tunability. Abstract : SrTiO3 –BaTiO3 nanocomposites with tailored microstructures exhibit enhanced dielectric properties in comparison to homogeneous ceramics with the same overall composition, including stable permittivity (830 ± 60) over a wide temperature range (−150 to 50 °C), low losses (≤3% between −150 to 150 °C), small dc conductivity (<10 −10 S m −1 ) and reasonable tunability (20% at 35 kV cm −1 ) with almost linear and weakly hysteretic behavior. The composites were fabricated from a SrTiO3 –BaTiO3 powder synthesized in situ using a multi-step aqueous solution process. The powder was consolidated using a high-pressure rapid field-assisted sintering method. Good densification without grain growth and only partial interdiffusion between the two perovskites was obtained. The enhanced dielectric properties largely originate from the existence of local composition gradients which determine a distribution of the Curie temperature and, consequently, the formation of a broad permittivity plateau. The fine-grained microstructure and the composite effect further contribute to suppress the temperature dependence of dielectric permittivity while retaining a reasonable tunability.